Accommodation and vergence function in children using atropine combined with orthokeratology. Issue 1 (February 2023) - Jiang, Jinyun; Long, Wen; Hu, Yin; Zhao, Feng; Zhao, Wenchen; Zheng, Bingru; Feng, Zhibin; Li, Zhouyue; Yang, Xiao
Abstract: Purpose: This study aimed to evaluate binocular vision in terms of vergence and accommodative measurements in children treated with 0.01% atropine combined with orthokeratology (OK). Methods: This was a prospective and randomized controlled clinical trial involving participants aged 8 to 12 years, with a spherical equivalent (SE) ranging from − 1.00 to − 6.00D. Participants were randomly divided into four groups: 1) a combination group using 0.01% atropine solution and OK lens; 2) an OK group using placebo solution and OK lens; 3) an atropine group using 0.01% atropine solution and wearing spectacles; and 4) a control group using placebo solution and wearing spectacles. Binocular vision was determined at baseline and at 3-month visits, with evaluations including horizontal phoria, fusional vergence, the accommodative convergence/accommodation (AC/A) ratio, accommodative lag, and accommodative amplitude (AA). The Wilcoxon signed-rank test was used to compare the changes in binocular vision in each group, and the Kruskal–Wallis test was used for comparisons of four groups. Results: Sixty-two participants completed the study. There was no significant difference in baseline refraction, accommodation or vergence measurements among the groups (all P > 0.05). Three months later, the accommodative lag significantly decreased in the OK group (P = 0.002) but remained unchanged in the other three groups (all P > 0.05). In addition, binocular accommodative facilities and positive relative accommodations increased in the combination and OK groups (both P < 0.05) but remained unchanged in the atropine and control groups (both P > 0.05). Only the participants with esophoria in the OK group had a significant decrease in esophoria (P = 0.008). Moreover, the changes in fusional vergence and AC/A did not significantly differ between the four groups (all P > 0.05). Conclusion: Accommodative measurements changed similarly in the groups treated with OK. Changes in vergence measurements after treatment with 0.01% atropine were not significant.